Association between Inflammation and Lower Urinary Tract Symptoms of Benign Prostatic Hyperplasia - Zhang, Qiang; Pang, Shiyu; Zhang, Yinglang; Jiang, Kang; Guo, Xuetao (Urology Journal, 2020)
Purpose: To evaluate the association between inflammation in prostatic tissue/serum sample and BPH-LUTS Patients and methods: The prostatic tissue and serum sample were collected from 183 patients who underwent transurethral plasmakinetic resection of the prostate (TUPKRP). The association between inflammation detected on prostatic tissues/ serum sample and LUTS related parameters, including International Prostate Symptom Score (IPSS) and peak flow rate (Qmax) were analyzed with SPSS version 13.0, and P-value <0.05 was chosen as the criterion for statistical significance. Results: There was a positive association between prostate tissue inflammation and LUTS. The differences of IPSS, VSS and SSS were seen with the increasing in grade of prostate tissue inflammation (P<.001; .001; =.014, respectively). Qmax and IPSS 12months after surgery were better in no inflammation group (P=.016; .031).Logistic regression analysis revealed a statistically association between the NEUT%?NLR and prostate tissue inflammation (P=.010; .004), but ROC curve showed the NEUT%, NEUT and NLR area under curve (.526; .452; .513, respectively) were calculated as <0.600. Patients with Qmax over 7.12 had more WBC count in peripheral blood (7.56±1.77 VS 6.37±1.86, P=.026). The NLR was significantly higher in the group of IPSS over 20 and AUR presence (P=.018; .017).The NEUT%, LYMPH%, LYMPH and NLR showed a statistically significance in different obstruction classification (P=.047; .046; .028; .014, respectively). Conclusion: There was correlation between chronic Inflammation and LUTS related to BPH. The patient without inflammation could acquire more sustained and steady relief than those with inflammation in LUTS related to BPH after TUPKRP.